A polycaprolactone/fish collagen/alginate biocomposite supplemented with phlorotannin for hard tissue regeneration. Issue 4 (12th January 2017) - Im, JeongHyeong; Choi, Chang Hyun; Mun, Frederick; Lee, JaeHwan; Kim, Hyunggun; Jung, Won-Kyo; Jang, Chul Ho; Kim, GeunHyung
Abstract : A biocomposite scaffold supplemented with collagen extracted from fish skin and phlorotannin from brown algae was proposed. Abstract : In tissue engineering, scaffolds have been widely studied for the purpose of regenerating damaged tissues or organs. Biocompatibility of materials, pore structure, and even growth factors are effective for enhancing cell growth and differentiation. In particular, mammalian collagen is biocompatible and hydrophilic, and provides good cell attachment due to interactions between Arg–Gly–Asp (RGD) domains and cell membranes. However, there have been some limitations on the use of mammalian collagen. In this study, we present a biocomposite scaffold supplemented with collagen extracted from fish skin and phlorotannin from brown algae. The effect of these biocomponents on various physical characteristics, including water wetting ability and tensile properties, was observed. The in vitro cellular activities of the biocomposites were examined using osteoblast-like cells (MG63) to assess cell proliferation and mineralization. The results show that the cells were more highly proliferated on the phlorotannin/fish collagen/alginate biocomposite compared to the control (collagen/alginate). Furthermore, the biocomposite showed significantly higher in vitro calcium deposition (38.37%) and osteogenesis (43.2%), determined by histomorphometric analysis, than the control. Based on these results, the biocomposite supplemented with fish collagen/phlorotannin was demonstrated to be a good potential biomaterial for enhancing bone tissue growth.